Ultrasonic evaluation of the bonding between non-metals EG composite to composite and of the bonding between 2 similar or dissimilar metals - Chan, Teck Soon (2018)
The use of adhesive in engineering products has prompt a need to evaluate the property of it without causing damage. Non-destructive testing (NDT) fits into this picture to deliver the ability to determine the properties of the material without depreciating it. In this project, the design of the test specimens follows closely with the American Society for Testing and Materials (ASTM) standards, D1002 for metal lap-joint and D5868 for composite lap-joint testing. Ultrasonic evaluation will be conducted using A-scan machine and techniques on the lap-joint area. The % screen of the first backecho and adhesive signal will be obtained from the display. The distance between them will also be read to calculate the acoustic velocity and density of the adhesive. Lastly, the test specimens will undergo intron lap-joint shear test to quantify the property of the adhesive by strength. The results show distinct difference in signals attained from a standard adhesive as compared to one which is subjected to contamination during production of the adhesive. However, it is also shown that ultrasonic evaluation using A-scan is ineffective in quantifying the strength of the adhesive. Although ultrasonic evaluation has shown to be effective in detecting the presence of defects in terms of water, dust and air contamination, further studies utilising different NDT techniques and analytical techniques may be required to effectively quantify the properties of the adhesive between two adherends.